2015
DOI: 10.5194/bgd-12-16803-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diurnal variation in the coupling of photosynthetic electron transport and carbon fixation in iron-limited phytoplankton in the NE subarctic Pacific

Abstract: Abstract. Active chlorophyll a fluorescence approaches, including fast repetition rate fluorometry (FRRF), have the potential to provide estimates of phytoplankton primary productivity at unprecedented spatial and temporal resolution. FRRF-derived productivity rates are based on estimates of charge separation at PSII (ETRRCII), which must be converted into ecologically relevant units of carbon fixation. Understanding sources of variability in the coupling of ETRRCII and carbon fixation provides physiological i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 76 publications
(104 reference statements)
7
56
1
Order By: Relevance
“…, the previously observed correlation from the Subarctic Pacific holds well for all samples taken from within the mixed layer. Both the Arctic phytoplankton assemblages we sampled here and the iron‐limited phytoplankton assemblages examined by Schuback et al () showed a very similar slope in the highly significant regression between the conversion factor and NPQ (Κ C /n PSII = 486 NPQ NSV + 1854; r 2 = 0.75, p < 0.01, df = 140). Moreover, the y‐intercept of this regression, 1854, is strikingly close to the theoretical minimum value of Κ C /n PSII (1600 e − C −1 Chl a RCII −1 , assuming 4 mol e − mol C −1 and 400 Chl a mol RCII −1 ).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…, the previously observed correlation from the Subarctic Pacific holds well for all samples taken from within the mixed layer. Both the Arctic phytoplankton assemblages we sampled here and the iron‐limited phytoplankton assemblages examined by Schuback et al () showed a very similar slope in the highly significant regression between the conversion factor and NPQ (Κ C /n PSII = 486 NPQ NSV + 1854; r 2 = 0.75, p < 0.01, df = 140). Moreover, the y‐intercept of this regression, 1854, is strikingly close to the theoretical minimum value of Κ C /n PSII (1600 e − C −1 Chl a RCII −1 , assuming 4 mol e − mol C −1 and 400 Chl a mol RCII −1 ).…”
Section: Resultssupporting
confidence: 72%
“…While our dataset is too small to draw general conclusions, our experimental approach allows us to gain some insight into how Arctic phytoplankton assemblages achieve optimal balance of the different components of the photosynthetic process. We also use our new observations to expand on recent work (Schuback et al ) exploring the feasibility of predicting the conversion factor between ETR RCII and 14 C‐uptake rates from FRRF derived estimates of non‐photochemical quenching (NPQ NSV ) in the pigment antenna.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…, Schuback et al. ). Under relatively steady light exposure, high light acclimated cells/organisms have much larger xanthophyll pools (Dd+Dt or Z+A+V), often leading to a greater capacity for XC‐mediated NPQ in both plants (Demmig‐Adams et al.…”
Section: What Is the Xanthophyll Cycle (Xc)‐related Nonphotochemical mentioning
confidence: 99%